The Impact of Interest Rates and Inflation Rates on Increasing the Number of Customers Saving - Richna Handriyani; Siti Junaida Hasibuan; Herlin Munthe (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2023)
This research investigates the impact of interest rates and inflation on the customer base of PT. Medan Independent Bank in terms of savings. The present study aims to examine the impact of interest rates and inflation on the customer base of Bank Mandiri (Persero) Medan. This study aims to examine the impact of interest rates and inflation on the customer base of Bank Mandiri (Persero) Medan in terms of savings. This study used a causal-comparative research design, which is a type of research that examines the cause-and-effect relationship between two or more variables. This study employs many data analysis approaches, including Validity and Reliability Tests, classical assumption tests, multiple linear regression, hypothesis testing, simultaneous tests, and the Coefficient of Determination (R2). The statistical findings show a significant relationship between the interest rate and the number of customers. This conclusion is based on the t-test (partial), where the calculated t-value of 5.039 exceeds the critical t-value of 2.920, and the significance level of 0.001 is less than the predetermined threshold of 0.05. Therefore, each interest rate significantly impacts the number of customers. Based on the obtained results, inflation substantially influences customer numbers. This conclusion is drawn from the t-test (partial) analysis, where the calculated t-value of 4.051 exceeds the critical t-value of 2.920 at a significance level of 0.001, which is lower than the conventional threshold of 0.05. Hence, individually and independently, inflation significantly impacts the number of customers. Based on the statistical findings, interest rates, and inflation substantially influence customer numbers. This assertion is supported by the F (simultaneous) test, where the F-count value of 18.348 exceeds the critical F-table value of 9.55, and the significance level of 0.000 is less than the predetermined threshold of 0.05. Hence, both interest rates and inflation significantly impact the number of customers concurrently.